Studi Eksplanatori Mengenai Pengaruh Iklim Komunikasi Organisasi Terhadap Kepuasan Kerja Tenaga Kependidikan Pasca Penerapan Pola Karir Jabatan Fungsional Pada Salah Satu Universitas di Kota Bandung - Dhea Perdana Coenraad; Ester Manik; Haris Nurdiansyah (Majalah Bisnis & IPTEK, 2020)
This study aims to discover the significance of the influence of organizational communication climate which consists of (1) trust, (2) joint decision making, (3) honesty, (4) openness in downward communication, (5) listening in upward communication, and ( 6) attention to high-performance goals for job satisfaction of teaching staff at Padjadjaran University. This study uses a quantitative approach with an explanatory survey method, which aims to obtain an explanation of the causal relationship between the research variables carried out through inferential statistical testing of path analysis. The population in this study was 1661 civil servants at Padjadjaran University, then the sample was determined based on the Taro Yamane formula as many as 325 respondents. The research results show that the variables of trust, honesty, and attention to high-performance goals have a significant effect on the job satisfaction of teaching staff at Padjadjaran University. Meanwhile, the variables of joint decision-making, openness in downward communication, and listening in upward communication did not have a significant effect. Still, they gave a positive contribution to the job satisfaction of teaching staff at Padjadjaran University. The results showed that the influence of organizational communication climate on job satisfaction of teaching staff at Padjadjaran University was 63.20%. This study concludes that there is a significant influence of organizational communication climate, either directly or indirectly, on the job satisfaction of teaching staff at Padjadjaran University.